Impacts of bark and foliage harvest on Khaya senegalensis (Meliaceae) reproductive performance in Benin - Gaoue, Orou G.; Ticktin, Tamara (The Journal of applied ecology, 2008)
1. Increasing concern over the sustainability of harvesting non-timber forest products (NTFP) has led to a growing literature on the ecological impacts of NTFP extraction. A large proportion of NTFP are harvested for multiple plant parts, but few studies have assessed the impacts of harvesting multi-use species. In addition, few studies have assessed how harvest effects may vary across space. This information is necessary for designing effective conservation plans for the many NTFP species that are harvested from variable ecological contexts. 2. This study assessed the impacts of combined bark and foliage harvest on Khaya senegalensis (Meliaceae) reproductive performance in Benin. K. senegalensis bark is an important medicine for malaria, the leaves are pruned by indigenous Fulani herders as a critical source of fodder for their livestock, and the timber is highly prized. Data on reproductive characteristics were collected from 12 populations spread across two ecological regions (Sudanian and Sudano-Guinean). Half the populations had a history of high harvest intensity and half were subject to low/no harvest. 3. Trees produced more fruit and began fruiting at a significantly smaller size in the drier Sudanian region than in the wetter Sudano-Guinean region. However, pruning decreased fruit production significantly in the Sudanian region but not in the Sudano-Guinean region. Pruning had a significantly greater impact on fruit production in larger trees than in smaller trees. High harvest populations in the Sudano-Guinean region had significantly higher rates of seed production than low harvest populations, although the seeds were significantly lighter. There were no significant effects of debarking or combined debarking and pruning on reproductive performance. 4. Synthesis and applications. This study illustrates that heavy rates of foliage harvest can decrease rates and patterns of reproduction in K. senegalensis, and that the impacts may vary across environmental contexts. Lowered rates of reproduction may lead to decreases in K. senegalensis population size over the long term. Effective ex situ conservation strategies for K. senegalensis include increasing the availability of its fodder and bark by promoting K. senegalensis plantations programmes involving Fulani harvesters.